Cytological investigation on interspecific progenies of red fleshed Saccharum robustum - Chandran, K; R, Athira; Lekshmi, Mayalekshmi; M, Nisha; B, Mahendran; R, Gopi (Journal of Sugarcane Research, 2021)
Saccharum robustum is one of the wild species and its chromosome number ranges from 2n =60 to 200. This group of S.robustum clones exhibit red flesh colour, robust growth and tolerance to abiotic stresses. In this study, 27 hybrid progenies developed from two polycrosses ‘involving’ red fleshed S.robustum clones were used as experimental material. The progenies were grouped into six categories based on the flesh colour and the cytological information was correlated. Six cytological groups were observed in the progenies. It was observed that all six progenies of NG 77-76 were of 2n=70 cytotype but among the progenies of NG 77-84, 57.1% were with 2n=70, 23.8% were with 2n=72 and the remaining four types were available in 0.83%. From this it is concluded that more cytotypes can be developed using NG 77-84 as female parent compared to NG 77-76. When the flesh colour was correlated with the diploid chromosome number, a significant negative correlation was observed. It is also inferred that the only one progeny having red flesh colour and 2n=60, might have developed as a result of un-intentional selfing.